Revealing The Concept Of Ahara Vidhi Visheshayatana In Modern - Sharma, Rashi; Kumar, Sunil (International Research Journal of Ayurveda & Yoga, 2024)
Ayurveda is one of the oldest healthcare systems which emphasizes on protecting the health of a healthy human being and taking care of diseased too. Health is basically a balance between three fundamental states i.e. Physical, Mental and Spiritual states and their relationship with the external environment. Ahara(food) which we eat is one of the most important and foremost content of Tri Upastambha(Ahara, Nidra and Brahmacharya). Ahara acts as a relationship manager between internal body and external environment. Classical texts of Ayurveda cover an array of themes on food. Charaka Samhita has very scientifically explained the Ahara vidhi visheshayatana which enlightens qualitative characteristics of food, its processing manners, combinations, quantity, seasonal variations ,dietary rules.This paper can reinvent the concepts of health and nutrition in Ayurveda and develop a healthy perspective in Digestive distress ultimately leads to several diseases of unknown etiology. If we adapt these rules of diet in our regime we can protect ourselves from such disorders. advanced era of systems biology.In today’s era due to lack of knowledge about concept of Ahara vidhi visheshayatana(Rules of Eating) , individuals are facing Digestive distress. The